“Something Could Happen to You at Any Moment”: Safety, Strategy, and Solidarity Among Trans and Nonbinary Protesters Against Police Violence - Osborn, Max (Critical criminology (Richmond, B.C.), 2023)
Transgender and nonbinary populations have a long history of being targeted for police surveillance, enforcement, and violence. The 2020 protest movement, which focused on racial justice and ending police violence more broadly, also included increased attention toward combating harm against transgender people, particularly trans people of color. This analysis, which draws on data from qualitative interviews with 31 transgender and nonbinary people in New York City (age 21–56, mean age = 31), explores participants’ attitudes about and involvement with the 2020 protest movement. Topics discussed include trans and nonbinary protesters’ decision-making processes, safety concerns, strategies used to manage risk at protests, and ways in which the protests helped shape their opinions about police and activism. In addition to navigating the same risks as any other protesters, trans and nonbinary people faced additional concerns and vulnerabilities specifically related to gender identity and presentation.